The Influence of the Problem-Based Learning (PBL) Model on Students’ Active Participation in the Pancasila Education Subject at Elementary School - Asmaul Husna, Vinanda; Genisa, Tiara; Syadira, Riri; Maulidia, Rani; Maylanda, Refina; Ajma'in, Syazwana Nur Amalina; Reinita, Reinita; Salmaini, Salmaini (TOFEDU: The Future of Education Journal, 2025)
Pancasila Education learning in elementary schools often faces challenges in increasing students’ active engagement. One method that can address this issue is the Problem-Based Learning (PBL) model, which focuses on solving real-world problems to encourage student participation. This study aims to examine the influence of the PBL model on students’ active involvement in Pancasila Education subjects. The research employs a literature review method by analyzing 10 scientific journals and research articles. Data collection was carried out through literature studies and document analysis, while data analysis applied a descriptive-qualitative approach to identify patterns of findings from various sources. The results indicate that the PBL model can enhance students’ active engagement in learning through discussion, collaborative problem-solving, and increased responsibility in the learning process. Furthermore, the implementation of PBL also supports students in developing critical thinking skills and understanding the values of Pancasila in everyday life.